PENGARUH PENYAJIAN LAPORAN KEUANGAN, AKSESIBILITAS DAN SISTEM AKUNTANSI KEUANGAN DAERAH TERHADAP AKUNTABILITAS PENGELOLAAN KEUANGAN DAERAH (studi empiris pada satuan kerja perangkat daerah Kabupaten Sijunjung) - Superdi '; M. Rasuli '; Alfiati Silfi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This study aims to research the influence of the presentation of financial report, accessibility and regional financial accounting system to accountability of regional financial management. The research was conducted on SKPD Sijunjung regency. The population in this study totaling 25 units working unit. Respondents in this study is the Head SKPD as users of the budget, the Head of Finance, Treasurer SKPD and parties that are directly related to the financial management of the Regional Government Sijunjung. Data analysis technique used is multiple linear regression analysis and t test using SPSS. The results showed the presentation of financial statements, accessibility and regional financial accounting system affect the accountability of financial management with the value of determination (Adjusted R2) amounted to 60.9% while the remaining 39.1% be affected by other variables not examined in this study.Keyword: accountability of the management of regional financial, the presentation of financial report, accessibility and regional financial accounting system